1990
DOI: 10.1002/eji.1830200111
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor‐negative thymocytes from SCID mice can be induced to enter the CD4/CD8 differentiation pathway

Abstract: In order to investigate the role of T cell receptor (TcR) expression in thymocyte maturation, we have analyzed thymocytes from C.B-17/SCID mice, which are unable to productively rearrange their antigen receptor genes and fail to express TcR. Despite this defect, SCID thymocytes are functional as they produce lymphokines and proliferate in response to a variety of stimuli. Phenotypic analysis revealed that thymocyte populations from young adult SCID mice resemble thymocyte populations from normal embryonic mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 48 publications
(10 reference statements)
7
38
0
Order By: Relevance
“…The latter results corresponded to our observation that addition of anti-CD3e mAb to fetal thymic organ cultures inhibited functional rearrangements of the TCR-0 locus while it accelerated induction of DP cells (11). On the other hand, other previous experiments had indicated that maturation to the DP stage could be induced in TCR-0-deficient thymorytes by transfer of syngeneic TCR+ cells (20). These latter results suggested that maturation to the DP stage did not require direct induction through TCR-O-CD3 but occurred by recruitment as soon as some TCR+ cells had been generated in the thymus.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The latter results corresponded to our observation that addition of anti-CD3e mAb to fetal thymic organ cultures inhibited functional rearrangements of the TCR-0 locus while it accelerated induction of DP cells (11). On the other hand, other previous experiments had indicated that maturation to the DP stage could be induced in TCR-0-deficient thymorytes by transfer of syngeneic TCR+ cells (20). These latter results suggested that maturation to the DP stage did not require direct induction through TCR-O-CD3 but occurred by recruitment as soon as some TCR+ cells had been generated in the thymus.…”
supporting
confidence: 91%
“…This hypothesis predicts that all DP cells show a productive rearrangement ofthe TCR-(3 locus. On the other hand, an earlier study showed that transplantation of normal bone marrow into SCID mice gave rise to both donor-derived TCR+ thymocytes and host-derived CD4+8+TCR -SCID thymocytes (20). It was hypothesized that the presence of TCR+ thymocytes would recruit SCIDderived DN cells into the developmental process, even though these cells do not themselves show functional rearrangement of the TCR-a locus .…”
Section: Duringembryogenesis T Lineage Committed Lymphoidmentioning
confidence: 99%
“…Both quantitative and qualitative differences may exist between the various CD3-ITAMs with respect to their ability to interact with distinct kinases and adaptors (69,70), and the present data predict that CD3␥ contributes primarily in a quantitative manner to TCR signaling. It remains to be investigated whether a TCR lacking the CD3␥-ITAM couples differentially to cytosolic substrates and signaling pathways.…”
Section: Discussionsupporting
confidence: 57%
“…A failure of the pre-TCR signaling, as in scid, RAG-1 Ϫ/Ϫ , or RAG-2 Ϫ/Ϫ mice that cannot rearrange TCR genes, results in an arrest at the DN3 stage of development accompanying with apoptosis (3)(4)(5)(6). As expected, introduction of the functional TCR␤-chain into those mice can rescue the transition from DN3 to DP stage and prevent apoptosis (6 -8).…”
mentioning
confidence: 71%